Facet joint degeneration in adolescent idiopathic scoliosis - Daniel G. Bisson; Polly Lama; Fahad Abduljabbar; Derek H. Rosenzweig; Neil Saran; Jean A. Ouellet; Lisbet Haglund (JOR Spine, 2018)
Adolescent idiopathic scoliosis (AIS) is a poorly understood deformity of the thoracolumbar spine which affects the intervertebral discs (IVDs) and the articular facet joints. The knowledge concerning facet joints in this context is very limited, although facet joint degeneration is a known contributor of back pain. In this study, a comprehensive investigation was performed to characterize the facet joint chondrocytes and extracellular matrix within the scoliotic spine. Surgically removed articular facet joint tissues were collected from patients undergoing spinal corrective surgery for AIS deformities, while non‐scoliotic articular facet joint tissues were obtained from cadaveric organ donors. Alterations in cartilage tissue structure were evaluated histologically with safranin‐O fast green and a modified OARSI grading scale. Pro‐inflammatory cytokines, matrix‐degrading proteases, and fragmented matrix molecules associated with cartilage degradation were analyzed by immunohistochemistry and western blotting. Safranin‐O fast green staining revealed that young scoliotic facet joints show clear signs of degeneration with substantial proteoglycan loss, similar to osteoarthritis (OA). The proteoglycan levels were significantly lower than in healthy asymptomatic non‐scoliotic control individuals. In comparison to controls, scoliotic articular facets showed increased cell density, increased expression of the proliferation marker Ki‐67, and higher expression of MMP‐3, MMP‐13, and IL‐1β. Expression and fragmentation of the small leucine‐rich proteins (SLRPs) chondroadherin, decorin, biglycan, lumican, and fibromodulin were analyzed with western blot. Chondroadherin and decorin were fragmented in cartilage from patients with a curve greater than 70°, whereas biglycan and fibromodulin did not show curve‐related fragmentation. AIS facet joint cartilage shows hallmarks of OA including proteoglycan loss, overexpression of pro‐inflammatory mediators, increased synthesis of matrix‐degrading proteases and fragmentation of SLRPs. As with patients with age‐related OA, the premature joint degeneration seen in scoliotic patients is likely to contribute to the pain perceived in some individuals.